Security Concerns of OCDMA System - Mandeep Singh, Navneet Chaudhry (International Journal of Advanced Science and Technology, 2020)
OCDMA(Optical code division multiple access) technology which is used for high-volume, highquality reliable full asynchronous multipleinformation accesed under decentralized network control. Due to which it is secure than other optical networks, OCDMA is easy to intercept with the data. OCDMA networks has a issue with the photonic layer.The eavesdropper can attack on the physical layer to retrieve the data and to disrupt communication by the jammer. So in this paper optical layer security has to be increasedin OCDMA network through signal availability in jam. The OCDMA transmission can be disrupted by high power jammer through transmitting the authorized user’s waveband. By technique which is known as anti jammingis used to slow down the effects of jammer by wavelength conversion principle. An OCDMA network has to be simulated with wavelength converter and even transmitted in the presence of high power jammer.